Ion yields in HIGISOL experiments based on JYFLTRAP data and PACE4 simulations : based on JYFLTRAP data and PACE4 simulations - Vainio, Laura (2012)
The purpose of this thesis was to calculate ion yields in the neutron-deficient mass region A=78-111 in heavy-ion ion-guide experiments at the Ion Guide Isotope Separator On-Line (IGISOL) facility in the Accelerator Laboratory of the University of Jyväskylä. The biggest challenge was that the experiments were not designed for yield calculations but for precision mass measurements. Therefore, only a small fraction of the available data could be used. The results were compared to theoretical cross sections calculated with PACE4 code. Ion yields agreed roughly with the cross-section calculations: On the one hand, the ions with the highest cross sections were detected. On the other hand, ratios between calculated cross sections and measured ion rates differed in some cases even within the same file. Cross sections for measured isotopes were in general more than 1 mb. Stable isotopes, which are used for calibration and reference purposes, were detected although no calculated cross section existed. Finally, some cross-section calculations were performed in order to find reasonable beam, target and energy combinations for future measurements. Main focus was on extending the JYFLTRAP measurements in the neutron-deficient A=78-111 region. Masses of some nuclei are already known with a precision which will be difficult to beat. For many of the nuclei of interest the calculated cross sections were found to be too small in order to safely evaluate whether measuring would succeed or not. Based on PACE4 calculations, the most promising candidates for future measurements are for example 79Y, 81Zr, 82Zr, 83Nb, 84Nb, 96-98Ag, 100In and 101In.